24=3(a-1)-3(2a+2)

Simple and best practice solution for 24=3(a-1)-3(2a+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24=3(a-1)-3(2a+2) equation:


Simplifying
24 = 3(a + -1) + -3(2a + 2)

Reorder the terms:
24 = 3(-1 + a) + -3(2a + 2)
24 = (-1 * 3 + a * 3) + -3(2a + 2)
24 = (-3 + 3a) + -3(2a + 2)

Reorder the terms:
24 = -3 + 3a + -3(2 + 2a)
24 = -3 + 3a + (2 * -3 + 2a * -3)
24 = -3 + 3a + (-6 + -6a)

Reorder the terms:
24 = -3 + -6 + 3a + -6a

Combine like terms: -3 + -6 = -9
24 = -9 + 3a + -6a

Combine like terms: 3a + -6a = -3a
24 = -9 + -3a

Solving
24 = -9 + -3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3a' to each side of the equation.
24 + 3a = -9 + -3a + 3a

Combine like terms: -3a + 3a = 0
24 + 3a = -9 + 0
24 + 3a = -9

Add '-24' to each side of the equation.
24 + -24 + 3a = -9 + -24

Combine like terms: 24 + -24 = 0
0 + 3a = -9 + -24
3a = -9 + -24

Combine like terms: -9 + -24 = -33
3a = -33

Divide each side by '3'.
a = -11

Simplifying
a = -11

See similar equations:

| 4/5z=1-1/5z | | D=4t^2 | | 18x-32=7x+16 | | D=4(16)t^2 | | x^2-5=x+1 | | 9y-14-5y+9=0 | | 7h+14=9n+36-24 | | 3n+4=0 | | 29*11= | | 0.5x=7+12x | | 26+n=48 | | 2x(16x^2-40x+25)-8x^2*(5-4x)=0 | | =-x+4x-2 | | -12x+-18=44 | | -2=-2.5(4)+b | | 2g-20+8g=1-g | | (10^(-1/2))*(10^(5/2)) | | 5x^8=15x^6 | | -2k+2m=m | | 81-(8*11)= | | 5/7.5=7/? | | 16=nm | | x+y=3y-6 | | 81-(811)= | | 5x^2+32x+1=-7x+9 | | -6m=2(3n-1) | | 81-(8*9)= | | 4n+24n-12=-12-32n | | 27x-4=136 | | -8=-3(3)+b | | (2/x-7)-(4/3x-6) | | 2*x-2=4 |

Equations solver categories